Sexual ethics : a theological introduction - Salzman, Todd A.; Lawler, Michael G. (Georgetown University Press, 2012)
Two principles capture the essence of the Catholic tradition onsexual ethics: that each and every marriage act must remain open to the transmissionof life, and that any human genital act must occur within the framework of marriage. In the Catholic tradition, moral sexual activity is institutionalized within theconfines of marriage and procreation, and sexual morality is marital morality. But theologians Todd Salzman and Michael Lawlercontend that there is a disconnect between many of the Church's absolute sexualnorms and other theological and intellectual developments explicitly recognized ande.